Pengaruh Model Inside Outside Circle Berbantuan PowerPoint Interaktif terhadap Literasi Bahasa Siswa Sekolah Dasar - Pratama, Aulia Sari Putri; Sari, Yunita (Didaktika, 2025)
One of the challenges faced in education is the low level of language literacy among elementary school students. Language literacy is a skill in obtaining and processing information, which is important for every student to have. This research aims to determine the effect of the Inside Outside Circle (IOC) model assisted by interactive PowerPoint on the language literacy of elementary school students. The method used in this research is quantitative and carried out on fourth-grade students at Sultan Agung Islamic Elementary School 4. The design in this research is pre-experimental design with the type of research being one group pretest-posttest design. The research instrument includes a list of pre-research interview questions as well as a list of pre-test and post-test questions. The result of the research shows that there is an effect of the Inside Outside Circle model assisted by interactive PowerPoint on students’ language literacy. Evidenced by the sig. value (2-tailed) hypothesis test result paired-sample t-test is 0.000 0.05. It can also be seen that there is an increase in the average post-test result of students’ language literacy compared to the average pre-test of students’ language literacy, which is 72.28 from 55.64. In conclusion, there was a significant increase in students’ language literacy skills, indicating that the Inside Outside Circle model assisted by interactive PowerPoint can be an innovation for teachers to improve students’ language literacy. These results can be used by practitioners and teachers in dealing with similar problems with alternative combinations of models and appropriate media.